The Lyric Style of the Song Rahmatan Lil Alamin by Maher Zain (Stylistic Study) - Alya Nurul Firdaus; Mirwan Akhmad Taufiq; Atiq Mohammad Romdlon (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2025)
This research stems from the increasing interest in religious songs that blend spiritual messages with poetic elements. The purpose of this study is to analyze the stylistic features in the lyrics of Rahmatan Lil Alamin by Maher Zain using a stylistic approach. This qualitative descriptive research employs the stylistic theory by Gorys Keraf, focusing on language style elements such as rhetorical, comparative, and repetition styles. Data were collected through documentation techniques and analyzed using content analysis to identify and classify language styles found in the lyrics. The findings reveal that the lyrics employ a variety of language styles: comparative styles, such as similes and metaphors, are used to portray divinity and moral values; rhetorical styles, like rhetorical questions and hyperbole, emphasize spiritual longing; and repetition styles strengthen the emotional tone and the central theme of universal mercy. These stylistic devices not only enhance the aesthetic value of the lyrics but also deepen their religious meaning, making the song both artistically engaging and spiritually resonant.Â Keywords: Stylistics, Religious Song, Maher Zain, Arabic Language Style